Evaluation on Physical and Rheological Properties of Lignin as Modifier Asphalt Binder - Mohd Sukeri, Mohamad Rais; Mohd Yunus, Khairul Nizam (Recent Trends in Civil Engineering and Built Environment, 2024)
The research is to investigate the physical and rheological properties of lignin as a transformer asphalt binder with the workability of lignin as a renewable binding agent in asphalt mixtures. As the demand for petroleum-based binders is increasing from year to year, an alternative to replacing asphalt binders with natural binders has been studied by former researchers. This research investigates the workability of lignin as a renewable binding agent in asphalt binders. The feasibility of lignin was measured through several aspects such as its physical and rheological performance, for comparison between lignin transformer asphalt binder (LMAB) and conventional asphalt binder (CAB), and to determine the optimum percentage of lignin as a transformer in asphalt binder. A review analysis was performed based on previous studies to determine the feasibility of lignin as a renewable binder. Lignin compounds are high molecular weight aromatic polymer compounds that contain phenylpropane as the basic unit. Lignin is found in most plant-based biomass and it acts as an adhesive on plant cells so that the stems remain rigid and still. Lignin contains more than 25% renewable organic carbon and is one of the most waste polymers, mostly from industrial and agricultural activities. Data will be taken based on previous studies to find out the results based on the results of previous studies through review analysis methods. The previous study data to be taken care of on the laboratory tests involved to analyze physical and rheological performance (LMAB). Among the laboratory tests such as penetration tests and softening tests, which determine the physical performance. Other tests to determine rheological properties are the viscosity test, dynamic shear rheometer test (DSR), pressure aging vessel (PAV), rolling thin film oven (RTFO) which describe various aging conditions of LMAB and the most common test performed in the laboratory is bending beam rheometer (BBR) to find the effect of stiffness. Independent laboratory tests should be conducted in the future to study the use of lignin as a natural binder in asphalt mixtures as this will help future researchers obtain more accurate and specific results. It is hoped that in the future this study will continue to be conducted so that the solution to this problem can be overcome as best as possible.